Demystifying the diagnostic potentials of air-conducted ocular and cervical vestibular evoked myogenic potential test elicited by a custom-built chirp stimulus among patients with vestibular disorders - Abdallatif, Athar Mazen Rasmi (2024)
The vestibular evoked myogenic potential (VEMP) is a clinical method to assess the function of otolith organs. VEMP is typically recorded with the 500 Hz tone burst, however, a chirp stimulus, initially designed for auditory brainstem responses, is being used to explore VEMP's diagnostic potential. This study explores the diagnostic potential of an air conducted downward narrowband chirp stimulus in detecting vestibular disorders using cervical VEMP (cVEMP) and ocular VEMP (oVEMP). In the initial stage, two pilot studies involving 25 healthy adults for cVEMP (Pilot 1) and 35 healthy adults for oVEMP (Pilot 2) were conducted to identify the optimal chirp stimulus. The optimal stimulus from the pilot studies was then compared with the 500 Hz tone burst stimulus in cVEMP and oVEMP responses in the subsequent case control experiment. The cVEMP testing was conducted on 55 healthy adults with a mean age of 29.5 ± 9.1 years and 43 patients with vestibular disorders with a mean age of 41.6 ± 8.9 years. On the other hand, the oVEMP testing was performed on 60 healthy adults with a mean age of 28.0 ± 7.3 years and 28 patients with vestibular disorders with a mean age of 41.5 ± 8.5 years. The two pilot studies revealed that the (1000-100) Hz chirp stimulus produced significantly higher amplitudes and shorter latencies of P1 and N1 for both cVEMP and oVEMP compared to the (1000-500) Hz chirp stimulus (p < 0.05). The (1000-100) Hz chirp stimulus was chosen to be used in the subsequent study. Results revealed that the (1000-100) Hz chirp stimulus generated significantly shorter latencies and larger amplitudes than the 500 Hz tone burst stimulus in the cVEMP testing (p <0.05). Likewise, the chirp stimulus elicited significantly shorter P1 and N1 latencies compared to the 500 Hz tone burst in the oVEMP testing (p <0.05). Receiver operating characteristic (ROC) analysis demonstrated the superior performance of the chirp stimulus for identifying patients with vestibular disorders. The chirp stimulus revealed a higher area under the curve (AUC), sensitivity, and specificity for both cVEMP and oVEMP tests compared to the tone burst. For cVEMP, the chirp's sensitivity ranged from 60.8% to 88.2%, and specificity from 38.7% to 87.7%, exceeding those of the tone burst (sensitivity: 51.5% to 89.7%, specificity: 40.3% to 87.4%). Similarly, oVEMP chirp’s sensitivity and specificity were 71.4% to 100.0% and 32.0% to 95.2%, respectively, surpassing those of the tone burst with sensitivity ranged from 38.0% to 78.4%, and specificity ranged from 11.5% to 94.1%. In conclusion, compared to the conventional 500 Hz tone burst stimulus, the (1000-100) Hz chirp stimulus has better diagnostic abilities to identify patients with vestibular disorders. Due to its promising outcomes, this stimulus can be an alternative stimulus for recording cVEMP and oVEMP in clinical practice.